Localised dynactin protects growing microtubules to deliver oskar mRNA to the posterior cortex of the Drosophila oocyte - Ross Nieuwburg; Dmitry Nashchekin; Maximilian Jakobs; Andrew P Carter; Philipp Khuc Trong; Raymond E Goldstein; Daniel St Johnston (eLife, 2017)
The localisation of oskar mRNA to the posterior of the Drosophila oocyte defines where the abdomen and germ cells form in the embryo. Kinesin 1 transports oskar mRNA to the oocyte posterior along a polarised microtubule cytoskeleton that grows from non-centrosomal microtubule organising centres (ncMTOCs) along the anterior/lateral cortex. Here, we show that the formation of this polarised microtubule network also requires the posterior regulation of microtubule growth. A missense mutation in the dynactin Arp1 subunit causes most oskar mRNA to localise in the posterior cytoplasm rather than cortically. oskar mRNA transport and anchoring are normal in this mutant, but the microtubules fail to reach the posterior pole. Thus, dynactin acts as an anti-catastrophe factor that extends microtubule growth posteriorly. Kinesin 1 transports dynactin to the oocyte posterior, creating a positive feedback loop that increases the length and persistence of the posterior microtubules that deliver oskar mRNA to the cortex.